Stable Isotopes of Nitrate, Sulfate, and Carbonate in Soils From the Transantarctic Mountains, Antarctica: A Record of Atmospheric Deposition and Chemical Weathering - Diaz, Melisa A.; Li, Jianghanyang; Michalski, Greg; Darrah, Thomas H.; Adams, Byron J.; Wall, Diana H.; Hogg, Ian D.; Fierer, Noah; Welch, Susan A.; Gardner, Christopher B.; Lyons, W. Berry (Frontiers in Earth Science, 2020)
Soils in ice-free areas in Antarctica are recognized for their high salt concentrations and persistent arid conditions. While previous studies have investigated the distribution of salts and potential sources in the McMurdo Dry Valleys, logistical constraints have limited our investigation and understanding of salt dynamics within the Transantarctic Mountains. We focused on the Shackleton Glacier (85° S, 176° W), a major outlet glacier of the East Antarctic Ice Sheet located in the Central Transantarctic Mountains (CTAM), and collected surface soil samples from 10 ice-free areas. Concentrations of water-soluble nitrate (NO3–) and sulfate (SO42–) ranged from <0.2 to ∼150 μmol g–1 and <0.02 to ∼450 μmol g–1, respectively. In general, salt concentrations increased with distance inland and with elevation. However, concentrations also increased with distance from current glacial ice position. To understand the source and formation of these salts, we measured the stable isotopes of dissolved water-soluble NO3– and SO42–, and soil carbonate (HCO3 + CO3). δ15N-NO3 values ranged from −47.8 to 20.4‰ and, while all Δ17O-NO3 values are positive, they ranged from 15.7 to 45.9‰. δ34S-SO4 and δ18O-SO4 values ranged from 12.5 and 17.9‰ and −14.5 to −7.1‰, respectively. Total inorganic carbon isotopes in bulk soil samples ranged from 0.2 to 8.5‰ for δ13C and −38.8 to −9.6‰ for δ18O. A simple mixing model indicates that NO3– is primarily derived from the troposphere (0–70%) and stratosphere (30–100%). SO42– is primarily derived from secondary atmospheric sulfate (SAS) by the oxidation of reduced sulfur gases and compounds in the atmosphere by H2O2, carbonyl sulfide (COS), and ozone. Calcite and perhaps nahcolite (NaHCO3) are formed through both slow and rapid freezing and/or the evaporation/sublimation of HCO3 + CO3-rich fluids. Our results indicate that the origins of salts from ice-free areas within the CTAM represent a complex interplay of atmospheric deposition, chemical weathering, and post-depositional processes related to glacial history and persistent arid conditions. These findings have important implications for the use of these salts in deciphering past climate and atmospheric conditions, biological habitat suitability, glacial history, and can possibly aid in our future collective understanding of salt dynamics on Mars.